THE EFFECT OF SUPERVISION AND QUALITY OF WORK LIFE (QWL) ON THE TEACHER WORKING MOTIVATION AT NATIONAL ELEMENTARY SCHOOL BEKASI SELATAN DISTRICT - Listianingtyas Murgiwati; Matin; Siti Rochanah (Jurnal Tunas Bangsa, 2019)
The purpose of this research isto know aboutthe influence of supervision and Quality of Work Life (QWL) to the teacher’s motivation of work. To achieve these objectives, this study uses a quantitative approach and data collection technique using questioning form. The survey was conducted from December 2018until February 2019and involving 305 teachers from all national elementary school at District South Bekasi. The sample on this research is determined randomly by using the Slovinformula, andinvolved 173 teachers for test instruments. The results this study was findings: first, the existence of the positive influence of supervision directly and significantly to the teachers motivation of work with path coefficient 0.329. Second, the Quality of Work Life (QWL) positive directly influence to the teacher motivation of work with path coefficient 0.298. Third, the existence of supervision positive directly influence to the Quality of Work Life (QWL) with the coefficient 0.236.Based on the results of this research work, the teacher’smotivation can be improved by increasing the supervision of the principal that is capable of encouraging the development of motivation on teachers in carrying his duties as well as support teachers working environment is good.